Evaluación de la densidad de siembra sobre el crecimiento y supervivencia de post-larvas en raceway. - Sorroza, Lita Scarlett (My University, 2019)
The nursery rearing crop of Litopenaeus vannamei, in raceway improves survival and achieves an increasing resistance to recurrent disease in fattening ponds. The efficiency of this system depends on the crop density, balanced natural food, and water quality factors. For this reason, the aim was evaluate the effect of stocking density on the growth and survival of L. vannamei in three periods of 10 days culture cycles. The study population was 7,56 million of post-larvae in the PL-12 stage, with an average weight of 3,13 mg ± 0,16 mg, distributed in three tanks per production cycle. The post-larvae were stocked at 20 PL/L, 30 PL/L and 40 PL/L. The daily growth control was conducted by the gravimetric method and the population count by the volumetric method and the survival rate was calculated. The shrimp feed used had 45% protein the initial feed rate was 25% of the biomass, which then decreased at a rate of 1% per day, divided into 12 feedings per day. The final average weight of the post-larval at density of 20 PL/L, 30 PL/L and 40 PL/L was 27,00 mg ± 2,08 mg, 21,33 ± 2,09 mg and 17,67 ± 1,53 mg, respectively, obtaining significant differences between these weights (p ˂ 0,05). The survival of the post-larval at density was 96,98 ± 0,74% and 96,1 ± 1,07%, respectively without significant differences (p > 0,05). Finally, the growth and survival rate decreased when increasing the stocking density.
La eficiencia de todo sistema de cultivo depende de la densidad de siembra, alimentación natural, balanceada y factores de calidad agua. Por tal motivo, el objetivo del presente trabajo fue evaluar el efecto de la densidad de siembra en el crecimiento y supervivencia de L. vannamei en tres ciclos de producción de 10 días cada una. La población estudiada fue de 7 560 000 post-larvas, en el estadio PL-12, con un peso promedio de 3,13 mg ± 0,16 mg, distribuidos en tres tanques por cada ciclo de producción. Las post-larvas fueron sembradas a 20 PL/L, 30 PL/L y 40 PL/L. El control de crecimiento se realizó por el método gravimétrico y el conteo poblacional, por el método volumétrico, para el porcentaje de supervivencia. Se utilizó alimento balanceado con 45 % de proteína, con una tasa de alimentación inicial de 25 % de la biomasa, la cual disminuyó a razón de 1 % por día, distribuido en 12 frecuencias. El peso promedio final de las post-larvas a las densidades de 20 PL/L, 30 PL/L y 40 PL/L fue de 27,00 mg ± 2,08 mg, 21,33 mg ± 2,09 mg y 17,67 mg ± 1,53 mg. La supervivencia no mostro diferencia significativa en las dos densidades de siembra 96,98 % ± 0,74 % y 96,15 % ± 1,07 %, pero si en la última 92,63 % ± 1,15 %, respectivamente. Finalmente, el crecimiento y la supervivencia disminuyen con el aumento de la densidad de siembra.
Keywords: RACEWAY; LITOPENAEUS VANNAMEI; POST- LARVA